A Novel Approach for Secure overlay Image Selection in Steganography - Chandrashekhara, J; Vinay, S (International Journal of Computer Sciences and Engineering, 2023)
Steganography is a technique for obscuring sensitive data in images or other media so that it cannot be accessed by nefarious parties. Image steganography hides secret messages inside pictures so only the person sending the message and the one receiving it can see what it says. Image steganography uses images to hide extra data by including or changing its image bits. We came up with a new way to share information called "Novel LSB Method” (NLSBM). It starts by turning the words into a picture so that it`s safe to share. This means that the way the text looks is changed, but the actual words stay the same. This is done to ensure that the text is safe when it is sent. You can use different types of pictures, like black and white or colourful, to do secure transmission. Our new way of hiding messages is really helpful because you don`t need another picture to hide your message in. Also, it is small and very fast compared to older methods.